Assessment of the use and need for an integrated molecular surveillance of tuberculosis: an online survey in Germany - Andrea Sanchini; Marta Andrés; Lena Fiebig; Stefan Albrecht; Barbara Hauer; Walter Haas (BMC, 2019)
Abstract Background The implementation of an integrated molecular surveillance (IMS) of tuberculosis (TB) is of high priority for TB control. IMS is defined as the systematic inclusion of molecular typing results in the national TB surveillance system. Although not standardized, an IMS of TB is already implemented in several low TB incidence countries. Germany is in the process of implementing a nationwide IMS of TB. This requires close collaboration between national and local health authorities. We conducted an online survey to understand the current use of molecular typing results for TB surveillance among the local public health offices (PHO)s in Germany, and to collect their perception and expectations towards the implementation of a nationwide IMS of TB. Methods The online survey was developed using the software Voxco and included 31 questions. The survey was sent to all the 377 local PHOs in Germany in April 2017. Responses were collected until June 2017. Results A total of 174/377 (46.2%) local PHOs participated in our survey, and 88/377 (23.3%) used molecular typing results in their routine TB surveillance work. The PHOs used molecular typing results especially as support for epidemiological contact tracing (62/88, 70.4%). We found statistically significant differences between answers of PHOs that did not use molecular typing results (n = 86) vs. PHOs that did use molecular typing results (n = 88): the latter perceived the use of molecular typing results as more beneficial for their work compared to the former (65.9% vs. 34.9%, p < 0.05). Moreover, the PHOs using molecular typing results expect for the future more support and coordination from regional and national public health institutes, especially regarding the identification and analysis of molecular clusters. Conclusions Our study is a step forward in the broader goal of implementing an IMS of TB in Germany. The local PHOs currently using the molecular typing results highlighted their positive attitude towards the implementation of an IMS, but also their needs of more support. Similar assessments might serve as an example for other countries which are on the way to implement a nationwide IMS of TB.